Addressing health of the black population in the health education - Ana Carolina Lino Silvério; Nicole Geovana Dias (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2019)
The study of the Health of the Black Population is important to identify and solve the issues that affect the health of this population, among them, racism. The Health of the Black Population is not a prioritized knowledge area in the courses of the Health area, although essential for the training of health professionals and for the black population itself. These shortcomings may indicate the non-recognition of the needs of this population impacting inequality indices. This study aims to find out, in the Health courses of the Federal University of Uberlândia, the existence of content on Health of the Black Population, such as disciplines, menus and teaching plans. As results we obtained few findings of approach of the Health of the Black Population. However, we present possible potentialities from which this important theme can be approached in the disciplines of the health courses.